基于SKETCH ENGINE的汉语近义词辨析研究 - Diana Constansz Sahertian (Bambuti, 2023)
Abstract This study aims to describe the similarities and differences in collocation behavior and semantic preferences between two synonymous Chinese verbs, hulüe (忽略) and hushi (忽视). The data derives from the Chinese Web 2017 (zhTenTen11) Simplified corpus in Sketch Engine. This study applies both quantitative and qualitative methodologies. The results of the research show that both synonymous words often collocate with abstract nouns, adverbs, verbs, adjectives and prepositions (“zai在”, “gei给”, “cong从”, “yu与”, “dui对”, “bei被”, “ba把”, “jiang将”). Some of them only collocate with “hulüe” or “hushi”, some collocate with both “hulüe” and “hushi”, but according to the frequency of occurrence, some tend to co-occur with one of them. Referring to Ucrel Semantic Analysis System, nouns classified in the "money and commerce in industry" domain tend to collocate with "hulüe", and nouns classified in the "body and individual" domain (especially "health and diseases” and “pharmacy and health care” ), and “education” domain tend to collocate with "hushi". Keywords: sketch engine; Chinese synonym; discrimination; hulüe; hushi; collocation behavior; semantic preference 摘要 本文通过Sketch Engine在线语料库里的Chinese Web 2017 (zhTenTen11) Simplified对汉语近义动词“忽略”和“忽视”在搭配行为和语义倾向方面进行辨析。本研究采用定性定量分析法。 通过分析得出“忽略”和“忽视”常与抽象名词、副词、动词、形容词和介词（“在”、“给”、“从”、“与”、“对”、“被”、“把”、“将”）搭配。其中有些只与“忽略”或“忽视”搭配，还有些与两个词搭配，但是按照出现频率，有些偏向于与其中一个共现。参照Ucrel 语义分析系统，归为“工业的金钱和商业”领域的名词倾向于与“忽略”搭配，而归为“身体和个体”领域（尤其有关“健康与疾病”和“药品与医疗”），以及“教育”领域的名词倾向于与“忽视”搭配。